Savannah the zebra fairy - Meadows, Daisy (Meadows, Daisy. Baby animal rescue fairies, 2015)
Savannah the zebra fairy needs Rachel and Kirsty's help to find a missing baby zebra before it ends up in Jack Frost's icy zoo.